The CRL4Cdt2 E3 ubiquitin ligase: a comprehensive review of its substrates, mechanisms, and roles in genomic stability - Murba, Afiqah Aimie; Ibrahim, Muhammad Aidil; Zakaria, Sarah Shazwani; Adenan, Nurul Hidayah; Jamaludin, Mohamad Ikhwan; Nishitani, Hideo; Ali, Mohd Shukuri Mohamad; Mazian, Mu’adz Ahmad (University of Malaya, 2026)
The CRL4Cdt2 ubiquitin ligase complex plays a pivotal role in maintaining genomic integrity and regulating the cell cycle, specifically during the S phase. By targeting key proteins such as Cdt1, p21, and Set8 for ubiquitination and degradation, CRL4Cdt2 ensures proper DNA replication and cell cycle progression. Dysregulation of this complex has been implicated in various cancers, including melanoma, breast cancer, gliomas, and ovarian cancer, where elevated levels of Cdc10-dependent transcript 2 (Cdt2) expression is often associated with poor prognosis and increased tumor aggressiveness. CRL4Cdt2 role extends beyond cell cycle regulation, as it also participates in the DNA damage response by degrading proteins like XPG, which is essential for nucleotide excision repair. Impaired CRL4Cdt2 function leads to DNA re-replication, genomic instability, and cancer progression. Recent studies have highlighted the therapeutic potential of targeting CRL4Cdt2 in cancer treatment, with inhibitors like pevonedistat showing promise in preclinical models. However, challenges remain, including the lack of a three-dimensional structure for Cdt2, which limits our understanding of its substrate recognition and degradation mechanisms. This review revisits the role of CRL4Cdt2 in regulating its cellular substrates, updated substrates targeted by CRL4Cdt2, explores its pathological consequences in cancer, and discusses potential therapeutic strategies to target this complex, offering new insights into its function and clinical relevance.